From conventional to innovative: fascia latae graft repair for ileal pouch prolapse: a case report - Capre-Pereira, Jessica; Gonzalez, Jorge-Ivan; Perez-Imbachi, Helber-Fabian; Posada, Eduardo; Kestenberg, Abraham (International Surgery Journal, 2025)
Ileal pouch prolapse (IPP) is a rare complication of total proctocolectomy reconstruction, usually managed with biological mesh, and although the use of autologous tissues represents a surgical alternative, there is little evidence in the literature about it. This report aims to present the case of a 29-year-old woman with familial adenomatous polyposis and total proctocolectomy, who presented with rectal pain and bleeding. She was diagnosed with IPP and was approached with fascia latae grafting, achieving symptomatic improvement and an uncomplicated postoperative course. This case highlights the use of autografts of the patient’s own tissues as a surgical alternative that generates a lower surgical cost with adequate clinical results.